Testing the gravity p-median model empirically. (December 2015) - Carling, Kenneth; Han, Mengjie; Håkansson, Johan; Rebreyend, Pascal
Abstract: Regarding the location of a facility, the presumption in the widely used p -median model is that the customer opts for the shortest route to the nearest facility. However, this assumption is problematic on free markets since the customer is presumed to gravitate to a facility by the distance to and the attractiveness of it. The recently introduced gravity p -median model offers an extension to the p -median model that account for this. The model is therefore potentially interesting, although it has not yet been implemented and tested empirically. In this paper, we have implemented the model in an empirical problem of locating vehicle inspections, locksmiths, and retail stores of vehicle spare-parts for the purpose of investigating its superiority to the p -median model. We found, however, the gravity p -median model to be of limited use for the problem of locating facilities as it either gives solutions similar to the p -median model, or it gives unstable solutions due to a non-concave objective function.